Redes feministas: movimentos de mulheres no século XXI a partir de suas insurgências nas redes sociais - Pagel, Geovana Cleni (2020)
This research aims to examine the regimes of meaning in the formation and connection of feminist networks, which can be mistaken for the emergence of the fourth feminist wave. One of the purposes of this study is to be able to contribute to this conception. The research corpus is comprised by a selection of 35 posts containing the hashtags of the campaigns #ChegadeFiuFiu [No More Catcalls] (2013) and #PrimeiroAssédio [First Harassment] (2015), from the NGO Think Olga, and the movement #EleNão [Not Him] (2018) on Twitter. Our intention is to identify the differences and dialogues established between the campaigns and observe changes in the experiences on social networks over six years, investigating the growing role of the internet in contexts of communication and social mobilization, through a critical perspective. The goal is to understand how feminist networks can engage individuals and groups of women, transitioning between online and offline environments (network and street). To address the concepts of network, multitude and micropolitics, the research is based mainly on such authors as Manuel Castells, Benjamin Loveluck, Antonio Negri, Michael Hardt and Suely Rolnik. For the corpus analysis, we employed Christine Mello’s extremities approach, which articulate the procedures of deconstruction, contamination and sharing as paths for interpretation. Feminisms in the extremities can be observed from three extreme edges: deconstruction associated with the woman's invisibility; contamination through the hashtag that attracts the viral and contaminates the network; and sharing as production of community and singularities. The research presents a brief history of the feminist movement, followed by reflections on the different feminist waves. To achieve this, a dialogue with such theorists as Silvia Federici, Angela Davis, bell hooks, Djamila Ribeiro, Carla Akotirene and Heloisa Buarque de Hollanda is established. Each new feminist wave is articulated as a disruption that seeks greater visibility and leadership for women. Social networks create intense flows of new mediations with contemporary feminisms, allowing for the re-signification of the woman as multitude, as network and as mediator of society. Feminist networks act as collective mediators of the multitude and transform the wide range of what it means to be a woman in the 21st century